Metode Penafsiran al-Qur’an M. Quraish Shihab - Muhammad Iqbal (Universitas Darussalam Gontor, 2010)
Nowadays, M. Quraish Shihab is a well known authoritative intellectual (ulama) of Qur’anic Tafsir in Indonesia and even in South East Asia. Started from his early age, he consistently devotes his life for this field. As the result, all his scientific works are solely based on Quranic studies. From this intensity of works, Quraish then formulates a tafsir method considered relevant to nowadays context. This paper is aimed to explore the method used by Quraish Shihab in Quranic tafsir. His method in Quranic tafsir is mostly mawdhu’I, even though he has finished a complete tafsir book for 30 Quranic sections which is arranged in tahlili. In his maudhu’I interpretation, Quraish prefers an ijtima’I style of tafsir, and considers the importance of linguistic approach. The latter is considered important to make the interpreter not forcing his interpretation outside of linguistic meaning as it will lead to the exploitation of Al-Quran. This linguistic approach is then combined with a view that Al-Quran is a unity and cannot be separated. In addition, Quraish also emphasizes on proportionality (munasabah) between one verse to another and between one surah to another.